THE EFFECT OF PLYOMETRIC TRAINING ON THE PHYSICAL READINESS OF FEMALE VOLLEYBALL PLAYERS - Mekhanet Mohamed; Chachou Ahmed Ali; Mokrani Djamel (Sport Scientific And Practical Aspects, 2025)
The aim of this study is to determine the importance of plyometric training in maintaining the physical readiness of top female volleyball players, as the study sample consisted of 20 f active in the Al-Nour Volleyball Club, Laghouat. In order to identify the extent to which plyometric training contributes to maintaining the physical readiness of volleyball players, we conducted physical tests and applied a training program, as the results of the statistical analysis showed that plyometric training contributes greatly to maintaining the physical readiness of senior volleyball players.